Applied reliability - Tobias, Paul A.; Trindade, David C. (Boca Raton, FL : CRC, 2012)
'This popular book is an easy-to-use guide that addresses basic descriptive statistics, reliability concepts, the exponential distribution, the Weibull distribution, the lognormal distribution, reliability data plotting, acceleration models, life test data analysis and systems models, and much more. The third edition includes a new chapter on Bayesian reliability analysis and expanded, updated coverage of repairable system modeling. Taking a practical and example-oriented approach to reliability analysis, it also provides detailed illustrations of software implementation throughout using several widely available software packages. Software and other files are available for download at www.crcpress.com'--
'It's been over 15 years since the publication of the 2nd edition of Applied Reliability. We continue to receive positive feedback from old users, and each year hundreds of engineers, quality specialists, and statisticians discover the book for the first time and become new fans. So why a 3rd edition? There are always new methods and techniques that update and improve upon older methods, but that was not the primary reason we felt the need to write a new edition. In the last 15 years, the ready availability of relatively inexpensive, powerful, statistical software has changed the way statisticians and engineers look at and analyze all kinds of data. Problems in reliability that were once difficult and time consuming for even experts now can be solved with a few well-chosen clicks of a mouse. Additionally, with the quantitative solution often comes a plethora of graphics that aid in understanding and presenting the results. All this power comes with a price, however. Software documentation has had difficulty keeping up with the enhanced functionality added to new releases, especially in specialized areas such as reliability analysis. Also, in some cases different well-known software packages use different methods and output different answers. An analyst needs to know how to use these programs effectively and which methods are the most highly recommended. This information is hard to find for industrial reliability problems'--
Pameran Fakulti/Nijuyon/Prof. Dr. Mohd. Raihan Taha
Includes bibliographical references (p. 551-556) and index.
Keywords: Reliability (Engineering); Quality control -- Statistical methods